Assessing benthic invertebrate vulnerability to ocean acidification and de-oxygenation in California: The importance of effective oceanographic monitoring networks - Meghan Zulian; Esther G. Kennedy; Sara L. Hamilton; Tessa M. Hill; Genece V. Grisby; Aurora M. Ricart; Eric Sanford; Ana K. Spalding; Manuel Delgado; Melissa Ward (PLoS ONE, 2025)
Greenhouse gas emissions from land-use change, fossil fuel, agriculture, transportation, and electricity sectors expose marine ecosystems to overlapping environmental stressors. Existing climate vulnerability assessment methods analyze the frequency of extreme conditions but often minimally consider how environmental data gaps hinder assessments. Here, we show an approach that assesses vulnerability and the uncertainty introduced by monitoring data gaps, using a case study of ocean acidification and deoxygenation in coastal California. We employ 5 million publicly available oceanographic observations and existing studies on species responses to low pH, low oxygen conditions to calculate vulnerability for six ecologically and economically valuable benthic invertebrate species: red sea urchin (Mesocentrotus franciscanus), purple sea urchin (Strongylocentrotus purpurpatus), warty sea cucumber (Apostichopus parvimensis), pink shrimp (Pandalus jordani), California spiny lobster (Panulirus interruptus), and Dungeness crab (Metacarncinus magister). Further, we evaluate the efficacy of current monitoring programs by examining how data gaps heighten associated uncertainty. We find that most organisms experience low oxygen (<35% saturation) conditions less frequently than low pH ( < 7.6) conditions. It is only deeper dwelling (>75 m depth) life stages such as Dungeness crab adults and pink shrimp embryos, juveniles, and adults that experience more frequent exposure to low oxygen conditions. Adult Dungeness crabs experience the strongest seasonal variation in exposure. Though these trends are intriguing, exposure remains low for most species despite well-documented pH and oxygen declines and strengthening upwelling in the central portions of the California Current. Seasonal biases of data collection and sparse observations near the benthos and at depths where organisms most frequently experience stressful conditions undermine exposure estimates. Herein we provide concrete examples of how pink shrimp and Dungeness crab fisheries may be impacted by our findings, and provide suggestions for incorporating oceanographic data into management plans. By limiting our scope to California waters and assessing the limitations presented by current monitoring coverage, this study aims to provide a granular, actionable framework that policymakers and managers can build from to prioritize targeted enhancements and sustained funding of oceanographic monitoring recommendations.